A postcolonial reading of Islam and imperialism in selected works of James Justinian Morier - Pouralifard, Akram (2014)
The attitude of the Orientalist world towards the legacy of the East is generally considered as one of the major trends of postcolonial criticism. From among several places of interest, Persia has long been at the center of consideration for such scholars for various reasons. One of the most noted and disputed Orientalists who has extensively studied Persia is James Justinian Morier (1780-1849), the British diplomat in Persia in early 19th century. A plethora of scholarly analyses have investigated Morier’s look at Persia for cultural and national concerns. However, his works have not been studied critically from a religious-cultural perspective. Therefore, the present study is an attempt to investigate five of Morier’s novels concerning Islam, Persia and the East, namely The Adventures of Hajji Baba of Ispahan (1824), The Adventures of Hajji Baba of Ispahan in England (1828), Ayesha, the Maid of Kars (1834), Zohrab the Hostage (1833), and The Mirza (1841), to survey the accuracy of the images rendered from Islam, the Prophet (pbuh), and the Muslims. Since Morier has commonly been considered as an Orientalist who is fair and objective in his writings, especially in the Hajji Baba sequel, his portrayals are generally assumed to be factual, even when documenting the cultural, national, social, or religious concerns. Edward Said’s perspective of the colonial discourse on the East is the major reference deployed in this investigation for its analysis. Said defines colonial discourse as the systematic discipline with which European culture was able to manage the Orient in its different phases. The occasional discrepancies of representations in the above mentioned novels, however, demand another critical framework which is resolved using Homi K. Bhabha’s theory of ambivalence in colonial stereotype. To explain this concept, Bhabha asserts that in colonial discourse analysis, the point of intervention should shift from the ready recognition of images as positive or negative, to an understanding of the processes of justification made possible through stereotypical discourse. So, for him, the colonial discourse permits a fluctuation in the interpretation of the images rendered by colonial writings. The findings of my study revealed previously unsaid facts about Morier’s representations. In his portrayal of the Muslim, the ‘stereotypical discourse’ gives way to a variety of praiseworthy and degenerate types of characters and there scarcely is a ready recognition of negative images. Morier’s representation of Islam and the Prophet (pbuh), however, is more applicable in demonstrating Said’s standpoint. For him, Islam and the Prophet (pbuh) suffer an irreparable degeneration compared to the Muslim, who is portrayed as capable of ‘administration and instruction’. This study’s findings show that Morier’s representation of the Muslim may, in many respects, be seen to be true, but his renderings of the Prophet(pbuh) and his judgment of Islam are a combination of misunderstandings and adversity, and therefore, cannot be accepted as scientific or reliable documentation.